2022
DOI: 10.1007/s40615-022-01474-5
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Culturally Tailored Education Programs for Black Communities with Cardiovascular Disease, Diabetes, Hypertension, and Stroke: Systematic Review Findings

Abstract: Background Community-based culturally tailored education (CBCTE) programs for chronic diseases may reduce health disparities; however, a synthesis across chronic diseases is lacking. We explored (1) the characteristics and outcomes of CBCTE programs and (2) which strategies for culturally appropriate interventions have been used in CBCTE programs, and how they have been implemented. Methods A systematic review was conducted by searching three databases to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 151 publications
0
0
0
3
Order By: Relevance
“…Indeed, even participants' references to community-based recruitment and engagement emphasized the role of family as community and family's role in increasing intervention acceptability. A family-based intervention reflects a culturally tailored approach to providing hypertension education and self-management support and is specifically a sociocultural strategy to cultural appropriateness (Kreuter et al, 2003) that positions discussions of hypertension and wellbeing in the social context and cultural values of persons racialized as Black or African American (Singh et al, 2022). Further, the family-level impact suggested by participants is supported in the literature: for example, Thornton et al (2019) found that African American adults' participation in a hypertension self-management intervention resulted in family-level changes to meal preparation and the food environment of the home and that role modeling healthy dietary behavior may benefit the healthy eating behaviors of coresidential adolescent children.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even participants' references to community-based recruitment and engagement emphasized the role of family as community and family's role in increasing intervention acceptability. A family-based intervention reflects a culturally tailored approach to providing hypertension education and self-management support and is specifically a sociocultural strategy to cultural appropriateness (Kreuter et al, 2003) that positions discussions of hypertension and wellbeing in the social context and cultural values of persons racialized as Black or African American (Singh et al, 2022). Further, the family-level impact suggested by participants is supported in the literature: for example, Thornton et al (2019) found that African American adults' participation in a hypertension self-management intervention resulted in family-level changes to meal preparation and the food environment of the home and that role modeling healthy dietary behavior may benefit the healthy eating behaviors of coresidential adolescent children.…”
Section: Discussionmentioning
confidence: 99%
“…No âmbito da educação cardiovascular, o foco principal reside em programas de educação cardiovascular comunitária (CBCTE), culturalmente adaptados, que são especificamente concebidos para satisfazer as complexas necessidades de saúde de adultos negros que sofrem de condições como doenças cardiovasculares, hipertensão, diabetes ou acidente vascular cerebral [6]. Estes programas adotam uma abordagem abrangente, enfatizando a importância de adaptar as intervenções para se alinharem às circunstâncias únicas de cada indivíduoincluindo as suas preferências alimentares, objetivos de saúde, rotinas de medicação e as barreiras que enfrentam devido às suas experiências de vida específicas [6].…”
Section: Que Tipos De Programas De Educação Cardiovascular Estão Impl...unclassified
“…Ao fazê-lo, os programas CBCTE visam elaborar uma estratégia educativa mais personalizada e eficaz que ressoe com os participantes a um nível mais profundo, aumentando assim o seu envolvimento e o potencial para melhores resultados de saúde [6]. Além disso, estes programas prestam especial atenção aos determinantes sociais da saúde, reconhecendo que factores como os níveis de rendimento e a educação podem influenciar significativamente a capacidade de um indivíduo para gerir as suas condições de saúde [6].…”
Section: Que Tipos De Programas De Educação Cardiovascular Estão Impl...unclassified
See 1 more Smart Citation